Left Atrial Rhythm in Cyanotic Congenital Heart Disease - Thaher Djalil; Otte J. Rachman; Hadi Purnomo; Bambang Madiyono (Indonesian Pediatric Society, 1978)
Report of two cases, one with DORV, and one with mirror image dextrocardia associated with TF.